High-Performance Dynamic Pattern Matching over Disordered Streams - Chandramouli, Badrish; Goldstein, Jonathan; Maier, David (International Conference on Very Large Databases (VLDB), Singapore, 2010)
Current pattern-detection proposals for streaming data recognize the need to move beyond a simple regular-expression model over strictly ordered input. We continue in this direction, relaxing restrictions present in some models, removing the requirement for ordered input, and permitting stream revisions (modification of prior events). Further, recognizing that patterns of interest in modern applications may change frequently over the lifetime of a query, we support updating of a pattern specification without blocking input or restarting the operator. Our new pattern operator (called AFA) is a streaming adaptation of a non-deterministic finite automaton (NFA) where additional schema-based user-defined information, called a register, is accessible to NFA transitions during execution. AFAs support dynamic patterns, where the pattern itself can change over time. We propose clean order-agnostic pattern-detection semantics for AFAs, with new algorithms that allow a very efficient implementation, while retaining significant expressiveness and supporting native handling of out-of-order input, stream revisions, dynamic patterns, and several optimizations. Experiments on Microsoft StreamInsight show that we achieve event rates of more than 200K events/sec (up to 5X better than simpler schemes). Our dynamic patterns give up to orders-of-magnitude better throughput than solutions such as operator restart, and our other optimizations are very effective, incurring low memory and latency.